An anthropological perspective on shifting cultivation: A case study of Khoriya cultivation in the Arun Valley of Eastern Nepal - Dhakal, Suresh (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 2,442 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v6i0.1104 Occasional Papers in Sociology and Anthropology Vol.6 2000 p.93-111